A study on the comfort and fit characteristics of the Polyester / Spandex running shorts - Santos, Nathania Erika Legaspi
The study is about fit and comfort of the fabrics used for the running shorts. This study got information from 15 women actively engaging in the sport of running who use running shorts for their sport. A survey was conducted with the Philippine National Team, University of the Philippines in Diliman, and the University of Santo Tomas in Manila. The athletes' expectations from the fabric of the shorts were used in determining the fit and comfort characteristics from the Nike Swift stretch shorts, style number 211411. This particular running shorts consists of materials from 81% polyester and 19% spandex for the front part of the shorts and a different fabric blend of 92% polyester and 8% spandex used for the back part of the running shorts. The Nike running shorts have an elastic waist band with a small pocket at the center back. Its leg opening has an elastic band to avoid riding up of the hem. This particular shorts helped the athletes understand how the Dri-FIT technology functions while they worked-out. The study was done by gathering the latest articles concerning the Dri-FIT technology of the running shorts. It also collected information from books about the principles of comfort and fit for more knowledge and understanding. The study also collected results that increase information on how athletes chose their running shorts. The research is about using the fabric's strength and dimensional stability to show proof on the fabric's abilities. The study was able to determine the athletes' requirements on how they chose their running shorts. Most of them wanted a pair of running shorts that can manage moisture, add comfort to the wearer, has an exact fit and breath-ability, does not ride up, have no restrictions while they move and inspire the athletes' performance while they run. The study was able to establish the athletes' expectations of the performance of the running shorts in relation to fit and comfort. At the same time, it helped the athletes understand how the dri-FIT technology functions while they run. Most of them liked the running shorts' fit to their waist because they can breathe properly. They like the shorts' fit on their buttocks and crotch because they were able to move unrestrictedly. Although some of them liked the idea of the banded leg opening, they feel that its fit wasn't excellent because it was restricting their muscles when it expands and contracts during work out. The small pocket at the center back of the running shorts was a good idea according to the respondents because they can keep their small things like car keys or bike keys and some cash in it. The fabric was able to wick sweat away from the body making the respondents feel dryness inside and out. The fabric's tightness was maintained even if it was wet with sweat and still kept the shorts in shape with the body. Therefore, the study was able to establish comfort and fit features of the fabric used in the running shorts.